Enhanced adsorption capacity of tetracycline on porous graphitic biochar with an ultra-large surface area. Issue 15 (3rd April 2023) - Huang, Bingyuan; Huang, Dan; Zheng, Qian; Yan, Changhan; Feng, Jiaping; Gao, Hejun; Fu, Hongquan; Liao, Yunwen
Abstract : 1. A ultra-large surface area of porous graphitic biochar was successfully using corn starch and ZnCl2 by a one-step method. 2. The adsorption capacity of tetracycline on the biochar could get 1122.2 mg g −1 at room temperature. Abstract : Excessive tetracycline in the water environment may lead to the harming of human and ecosystem health. Removing tetracycline antibiotics from aqueous solution is currently a most urgent issue. Porous graphitic biochar with an ultra-large surface area was successfully prepared by a one-step method. The effects of activation temperature, activation time, and activator dosage on the structural changes of biochar were investigated by scanning electron microscopy, Brunauer–Emmett–Teller, X-ray powder diffraction, and Raman spectroscopy. The effect of the structure change, adsorption time, temperature, initial pH, and co-existing ions on the tetracycline removal efficiency was also investigated. The results show that temperature had the most potent effect on the specific surface area, pore structure, and extent of graphitization. The ultra-large surface area and pore structure of biochar are critical to the removal of tetracycline. The q e of porous graphitic biochar could reach 1122.2 mg g −1 at room temperature. The calculations of density functional theory indicate that π–π stacking interaction and p–π stacking interaction can enhance the tetracycline adsorption on the ultra-large surface area of graphitic biochar.